Online Meetings: When Repetition Signals Engagement - Murat, Anais Claire; Vogel, Carl (IEEE, 2025)
Online meetings are challenging environments to assess and foster engagement. By observing the relationship between engagement and lexical spread in the RoomReader corpus, a dataset that records the engagement of 3-4 participants during online sessions moderated by a tutor, we find evidence that dialogue participants’ engagement increases with the tutor’s back-channeling whereas the participants’ production associates with significantly greater engagement when it reuses words from the previous turns and builds on ideas.
16th IEEE International Conference on Cognitive Infocommunications
PUBLISHED
Vienna, Austria
Keywords: interaction; online meeting; online tutoring; engagement; lexical spread; entropy; repetition; Digital Engagement; Digital Humanities; Inclusive Society; Telecommunications; Artificial Intelligence; Communication Sciences; Computational Linguistics; Discourse & Dialogue; Formal Semantics; Multi-modal analysis of dialogue; Pragmatics